2016
DOI: 10.1177/0734242x16632056
|View full text |Cite
|
Sign up to set email alerts
|

Municipal solid waste management in Tehran: Changes during the last 5 years

Abstract: The situation of waste management in Tehran was a typical example of it in developing countries. The amount of municipal solid waste has been increasing and the city has depended on landfill for municipal solid waste management. However, in recent years, various measures have been taken by the city, such as collecting recyclables at the source and increasing the capacity of wasteprocessing facilities. As a result, significant changes in the waste stream are starting to occur. This study investigated the nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…According to surveys of residents’ willingness to classify waste, Liu et al [ 18 ], Malmir et al [ 19 ], Wan et al [ 20 ] and Kirakozian [ 21 ] showed that waste-classification infrastructure will have an impact on residents’ willingness to participate in household waste classification, and its high quality, including convenience, is positively correlated with residents’ enthusiasm for participating in waste classification. Zhang et al [ 22 ] reported that low-quality waste-collection facilities will significantly reduce residents’ willingness to classify garbage when studying the current situation of the garbage sorting and recycling system in Chengdu.…”
Section: Research Hypothesismentioning
confidence: 99%
“…According to surveys of residents’ willingness to classify waste, Liu et al [ 18 ], Malmir et al [ 19 ], Wan et al [ 20 ] and Kirakozian [ 21 ] showed that waste-classification infrastructure will have an impact on residents’ willingness to participate in household waste classification, and its high quality, including convenience, is positively correlated with residents’ enthusiasm for participating in waste classification. Zhang et al [ 22 ] reported that low-quality waste-collection facilities will significantly reduce residents’ willingness to classify garbage when studying the current situation of the garbage sorting and recycling system in Chengdu.…”
Section: Research Hypothesismentioning
confidence: 99%
“…The collection and the disposal of RMSW are frequently unmanaged and unregulated in low-and middle-income nations [17,18]. Inadequate RMSW disposal or the lack of their management might lead to significant environmental issues posing adverse public health effects [7,18] and pollution problems in both developed and developing countries [19][20][21]. In many countries, waste offers a largely untapped supply of raw materials because resource recovery rates are still relatively low, despite the fact that recoverable materials make up the majority of the waste stream [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the parameter fits, only four categories were considered: 1) food waste, 2) yard waste, 3) paper, and 4) wood. The reason is to decrease the optimization variables and take into account the study by (T. Malmir et al, 2016) that categorized the biodegradable OW into different types: easily (e.g., food waste), slowly (e.g., paper), and hardly (e.g., wood, textiles, and leather) biodegradable wastes. 𝑘 𝐶𝐻 4 is the biodegradation half-life in years -1 for OW in a landfill and, based on the U.S. EPA, can range between 0.02 y -1 (less than 635 mm of precipitation) and 0.04 y -1 (more than 635 mm of precipitation) (Thompson et al, 2009).…”
Section: Ch 4 Modelingmentioning
confidence: 99%